Analisis Efisiensi Biaya Produksi Pada CV Cupu Artama Jaya Kabupaten Jombang - Hermanu, Nico Alfonso; Sedyati, Retna Ngesti; T, Tiara (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
Cost efficiency in production is crucial for companies to achieve optimal profitability. To optimize production costs, companies need to ensure cost efficiency to avoid unnecessary expenditures. One form of cost efficiency analysis in production involves employing standard cost analysis, which compares production cost expenditures with predetermined standard costs. A study on production cost efficiency was conducted at CV Cupu Artama Jaya in Jombang Regency. The objective was to assess the efficiency within the company. The research was carried out from October to November, focusing on the production of chicken fillets. The research methodology employed was descriptive quantitative analysis. The purposive area sampling technique was utilized, and data on cost efficiency were gathered through interviews and financial data collection during October and November. Data analysis revealed higher expenditures in October compared to in November was more efficient than the previous month with a total difference in the purchase price of raw materials of Rp54,857,608 and a difference in quantity of raw materials of Rp1,119,498,831 and difference in price or quantity experienced an inefficient condition with a difference Rp19,316,142. Meanwhile, labor costs in November showed normal results for the difference in labor wage rates and the difference in working hour efficiency, which showed a difference of Rp). The difference in factory overhead costs in November showed efficient results with a volume difference of Rp48,477,889.62 and the controlled difference showed normal conditions with a total difference of Rp0.